Performance of the Illumina GGP Bovine 100K SNP array for buffalo populations genotyping in Colombia - William Burgos-Paz; Yolanda Gómez-Vargas; Edison J. Ramírez-Toro (Revista Científica, 2023)
The selection of buffaloes in Colombia is primarily based on the assessment of genetic merit or performance testing. Despite the availability of buffalo-specific genotyping tools, their cost limits routine implementation for genomic selection in the country. Therefore, we conducted an evaluation of single nucleotide polymorphism (SNP) arrays originally designed for cattle to determine their potential applicability in genetic evaluation of Colombian buffalo populations. Eight DNA samples from buffalo individuals belonging to the Murrah, Mediterranean, and crossbred genetic groups were genotyped using the Illumina Bovine HD770K Array. SNPs that overlapped with the GGP-HD150K and GGP-LD30K microarrays (Illumina) were specifically selected considering commercial chip availability. Subsequently, 24 additional samples were analyzed using the GGP Bovine 100K array. Allele segregation, heterozygosity, genetic structure, and genomic association to weight at 25 months were calculated. Out of the 734,240 identified SNPs, 86,521 (11.7%) exhibited uniform segregation in buffaloes across chromosomes ranging from 10.8% for Chr11 to 12.5% in Chr 12. By extracting segregating SNPs in HD770K from the GGP-HD150K and GGP-LD30K chips, we identified 15,169 and 3,311 markers, respectively. Analysis using the GGP Bovine 100K revealed 5,995 segregating SNPs, of which 42.01% had Ho<=0.5. On average, the observed heterozygosity in buffaloes was higher than cattle. Genetic structure among the three included genetic groups was successfully detected using 2,519 SNPs (Ho<=0.5). Moreover, 6 and 20 SNPs with FDR 0.05 and 0.1 respectively, were associated with weight at 25 months, Notably, some of these SNPs located in genomic regions harboring genes such as SLC24A4 or RPUSD4 were previously reported associated with conformation traits or feed efficiency in cattle. Considering the current scenario, the cost- benefit ratio analysis favors use of the GGP Bovine 100K array, as an initial strategy to support genetic structure of the populations, parentage testing and future genomic evaluation trials in buffaloes.